BUSINESS PORTFOLIO RESTRUCTURING AT PT. DUTA INDO LESTARI - Ajeng Handayani Purwaningrum (Pascasarjana Universitas Riau Kepulauan, 2022)
The dynamic construction business climate, as well as high competition in the market, encourages the company to continue to grow and maintain its presence in the market. The company will develop certain products and businesses by entering into an industry that is related or not related to the core business, one of which is through a diversification strategy. However, this strategy often destroys existing value, as a result of over-diversification. PT Duta Indo Lestari is a private company that develops business in the construction and processing of concrete, located in Pontianak, West Kalimantan. PT Duta Indo Lestari needs an alternative strategy in the form of restructuring to optimize the performance of the business division. This study uses a qualitative descriptive method, and a little additional quantitative to calculate the score of industry attractiveness and competitive strength of business units. From the data analysis carried out, it is known that the right business portfolio restructuring for PT Duta Indo Lestari is to establish a new subsidiary to help manage the concrete business division, but still stick to the existing business lines and pursue the opportunities that exist in the business. It is hoped that this alternative strategy can help improve the performance of each business division and realize more efficient business operations.